Environmental, Social, Dan Governance Disclosure Terhadap Value Perusahaan - Hayati, Norma; Zoraya, Intan (Universitas Islam Kadiri, 2023)
This research aims to assess the impact of environmental, social and governance factors on company valuation. This research utilizes a sample of mining companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. Data analysis utilizes multiple regression analysis, with the independent variable represented by the ESG score and the dependent variable represented by firm value . The analysis was carried out using evwies 12. Research findings show that the implementation of Environmental and Social disclosures does not produce a statistically significant impact on company valuation. In the field of corporate affairs, it has been empirically shown that governance transparency practices have a major impact on overall company value.